Identifying putative Mycobacterium tuberculosis Rv2004c protein sequences that bind specifically to U937 macrophages and A549 epithelial cells (2005)
Virulence and immunity are still poorly understood in Mycobacterium tuberculo sis.TheH37RvM. tubercu-losis laboratory strain genome has been completely sequenced, and this along with proteomic technologyrepresent powerful tools contributing toward studying the biology of target cell interaction with a facultativebacillus and designing new strategies for controlling tuberculosis. Rv2004c is a putative M. tuberculosisprotein that could have specific mycobacterial functions. This study has revealed that the encoding gene ispresent in all mycobacterium species belonging to the M. tuberculosis complex. Rv2004c gene transcriptionwas observed in all of this complex’s strains except Mycobacterium bovis and Mycobacterium microti.Rv2004c protein expression was confirmed by using antibodies able to recognize a 54-kDa molecule byimmunoblotting, and its location was detected on the M. tuberculosis surface by transmission electronmicroscopy, suggesting that it is a mycobacterial surface protein. Binding assays led to recognizing highactivity binding peptides (HABP); five HABPs specifically bound to U937 cells, and six specifically boundto A549 cells. HABP circular dichroism suggested that they had an a-helical structure. HABP–target cellinteraction was determined to be specific and saturable ; some of them also displayed greater affinity for A549cells than U937 cells. The critical amino acids directly involved in their interaction with U937 cells were alsodetermined. Two probable receptor molecules were found on U937 cells and five on A549 for the twoHABPs analyzed. These observations have important biological significance for studying bacillus–target cellinteractions and implications for developing strategies for controlling this disease